A Systematic Literature Review of E-Government Evaluation - Mohammad Nurul Huda; Etry Novica Kurniasari; Siti Mas Ruroh (Universitas Muhammadiyah Malang, 2022)
The adoption of information and communication technology has had an effect on remodeling the general public service delivery system called e-government. E-government evaluation is a crucial aspect to evaluate how a long way the improvement in the quality of the public service delivery system provided by the technology. This study aim was to summarize and to decide the influencing factors in e-government evaluation by analyzing published scientific articles. This research method used a systematic literature review. The authors performed searches for scientific articles in online database Elsevier (Scopus) written in English and can be accessed in full paper. This study uses 18 articles of data to conduct a systematic literature review. The findings show that most previous studies on e-government service evaluation published in 2018 and 2020. The findings also show that developing countries are the most dominating research locations. In addition, the findings show the influencing factors in e-government evaluation are 1) user satisfaction consist of reliability/efficiency, compatibility, perceived of benefit, trust, responsiveness, overall satisfaction; 2) Site Quality consist of information quality, system quality, service quality, perceived usefulness, ease to use, accessibility, security and privacy, effectiveness, design, and content; 3) Facilitating condition consist of IT infrastructure. These twelve variables can be used as basis for future research to evaluate the quality of e-government. This study has limitations because it only uses the online database Elsevier (Scopus) as a database to obtain published scientific article data during 2014-2021.